The influence of external separate heating on the synchronization of Josephson junctions. Issue 5 (6th March 2014) - Grib, Alexander; Seidel, Paul
<x xml:space="preserve">Abstract</x> Recent experiments on synchronized radiation from intrinsic Josephson junctions in high‐temperature superconductors showed that the difference of temperatures of the junctions can influence synchronization. We investigated numerically the mechainsm of this influence on the example of two overdamped Josephson junctions loaded by a shunt consisting of the resistance and the inductance. We showed that strong synchronization of radiation was obtained by means of external separate heating/cooling of junctions. Due to the change of critical currents in the process of heating or cooling, the current–voltage (I–V) characteristics of the junctions cross each other and junctions are synchronized by the ac current in the load in the vicinity of this crossing. The maximal tolerant spread of critical currents for this mechanism of synchronization is 15–20% that is twice larger than the maximal tolerant spread for this system without the separate heating.<inline-graphic xlink:href="ark:/27927/pgh5js1bw" content-type="pssb201350256-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> I–V characteristics of two separately heated junctions. Phase locking in this system is impossible without heating for such large spreads of critical currents.